Probing the edge-related properties of atomically thin MoS2 at nanoscale - Teng-Xiang Huang (Nature Portfolio, 2019)
Probing inevitable defects in two- dimensional materials is challenging. Here, the authors tackle this issue by using tip-enhanced Raman spectroscopy (TERS) to obtain distinctly different Raman features of edge defects in atomically thin MoS2, and further probe their unique electronic properties as well as identify the armchair and zigzag edges.